Identification of Critical m6A RNA Methylation Regulators with Prognostic Value in Lower-Grade Glioma. - Zheng, Jianglin; Wang, Xuan; Qiu, Yue; Wang, Minjie; Yu, Hao; Zhou, Zijie; Wu, Zhipeng; Jiang, Xiaobing (BioMed Research International, 2021)
Increasing evidences have revealed that N6-methyladenosine (m6A) RNA methylation regulators participate in the tumorigenesis and development of multiple tumors. So far, there has been little comprehension about the effects of m6A RNA methylation regulators on lower-grade gliomas (LGG). Here, we systematically investigated the expression profiles and prognostic significance of 36 m6A RNA methylation regulators in LGG patients from the TCGA and CGGA databases. Most of the m6A RNA methylation regulators are differentially expressed in LGG tissues as compared with normal brain tissues and glioblastoma (GBM) tissues. The consensus clustering for these m6A RNA methylation regulators identified three clusters. Patients in cluster 3 exhibited worse prognosis. In addition, we constructed an m6A-related prognostic signature, which exhibited excellent performance in prognostic stratification of LGG patients according to the results of the Kaplan-Meier curves, ROC curves, and univariate and multivariate Cox regression analyses. In addition, a significant correlation was observed between the m6A-related prognostic signature and the immune landscape of the LGG microenvironment. The high-risk group exhibited higher immune scores, stromal scores, and ESTIMATE scores but lower tumor purity and lower abundance of activated NK cells. Moreover, the expression level of immune checkpoints was positively correlated with the risk score. To conclude, the current research systematically demonstrated the prognostic roles of m6A RNA methylation regulators in LGG.